1977
DOI: 10.1111/j.1464-410x.1977.tb04559.x
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Oestrogen-Escaped Carcionoma of the Prostate with Estramustine Phosphate

Abstract: 30 patients with oestrogen-escaped carcinoma of the prostate have been treated with estramustine phosphate (Estracyt). 27% showed a partial objective response and 33% had a subjective response. The terms used for defining a response are challenged and it is recommended that comparative controlled trials are necessary to judge the place of this drug in the management of advanced prostatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 5 publications
(3 reference statements)
1
7
0
Order By: Relevance
“…Although estramustine was not administered alone in this study, these data appear superior to those previously reported for hormoneresistant groups (Table 1). [26][27][28][29][30][31] The response rate of 70 percent in patients with stage D disease and no previous therapy is consistent with the results reported by others administering estramustine alone. 26.28.31-33 Clinical studies currently are in progress by the National Prostate Cancer Project to determine the efficacy of estramustine as an adjuvant to definitive surgery or radiotherapy in patients with newly diagnosed nonmetastatic cancer of the prostate."?"…”
Section: Clinical Studiessupporting
confidence: 81%
“…Although estramustine was not administered alone in this study, these data appear superior to those previously reported for hormoneresistant groups (Table 1). [26][27][28][29][30][31] The response rate of 70 percent in patients with stage D disease and no previous therapy is consistent with the results reported by others administering estramustine alone. 26.28.31-33 Clinical studies currently are in progress by the National Prostate Cancer Project to determine the efficacy of estramustine as an adjuvant to definitive surgery or radiotherapy in patients with newly diagnosed nonmetastatic cancer of the prostate."?"…”
Section: Clinical Studiessupporting
confidence: 81%
“…Although used widely, the efficacy of estramustine (Estracyt) has never been proven in controlled clinical trials. Subjective response rates of up to 35% have been reported (Leistenschneider and Nager, 1989;Chisholm et al, 1977), but this may be no better than second-line hormone therapy at the cost of greater toxicity (Johansen et al, 1991). Fracture of long bones is a common problem in patients with extensive bony disease.…”
Section: Symptomatic Relapsementioning
confidence: 99%
“…Also estramustine phosphate represents a high-dose estrogen treatment and acts probably also as a cytostatic agent. The drug has been shown to relieve pain and to improve the general condition in prostate cancer patients who progress on ongoing primary hormone manipula tions [21,22], According to the present study with admittedly few patients within each group, secondary hormone treatment with 1 of the above 3 hormonal agents reduces elevated PSA levels by > 50% in 20-30% of the patients with hor mone-resistant prostate cancer. These biochemical re sponses objectively indicate that at least some of the tumor cells are still sensitive for endocrine manipulation.…”
Section: Treatmentmentioning
confidence: 99%